Carbonylations of Alkenes in the Total Synthesis of Natural Compounds - Gehrtz, Paul H.; Hirschbeck, Vera; Ciszek, Benjamin; Fleischer, Ivana (Synthesis, 2016)
The goal of this review is to highlight the applications of carbonylation reactions of alkenes in the total synthesis of natural compounds. These highly atom-economic reactions, which are known for their industrial applications, constitute attractive synthetic methodologies for the selective construction of carbonyl compounds. We aimed at the selection of recent methodologically attractive syntheses where carbonylations were applied as key steps. In addition, a few examples of the related carbonylation of allenes are shown.1 Introduction2 Hydroformylation3 Hydroaminomethylation and Related Tandem Hydroformylation Reactions4 Reppe Carbonylation5 Allylic Carbonylation6 Oxidative Carbonylation7 Pauson–Khand Reaction8 Summary and Outlook
Keywords: total synthesis; alkenes; hydroformylation; carbonylation; Pauson–Khand reaction